Island divertor configuration design for a quasi-axisymmetric stellarator CFQS. (August 2020) - Okamura, S.; Liu, H.; Shimizu, A.; Kinoshita, S.; Isobe, M.; Xiong, G.; Xu, Y.
Abstract : A magnetic field configuration of an island divertor for a quasi-axisymmetric stellarator (CFQS) is proposed. The configuration incorporates large islands surrounding the core confinement region. The interface between the core region and the peripheral region of the island divertor is a clear magnetic separatrix similar to a tokamak divertor. The structure of divertor magnetic field lines is very regular without stochasticity and the connection length is sufficiently long for good divertor performance. Such a divertor configuration is produced in the magnetic field configuration for the CFQS device, which is now under construction in China.